Kyai Leadership Drives Sustainable Inclusive Education in Islamic Boarding Schools: Kepemimpinan Kyai Mendorong Pendidikan Inklusi Berkelanjutan di Pesantren - Firdaus , Aisy Hanif; Husna, Muhammad Ahsanul; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Inclusive education has emerged as a global commitment to educational equity, requiring institutions to accommodate learners with diverse abilities. Specific Background Islamic boarding schools in Indonesia occupy a strategic position in advancing this agenda due to the central authority of kyai leadership, yet empirical evidence on how such leadership operates within inclusive pesantren remains limited. Knowledge Gap Existing studies largely focus on formal schooling or pesantren traditions and curricula, leaving kyai leadership dynamics in inclusive Islamic education underexplored. Aims This study aims to analyze how kyai leadership shapes and sustains inclusive education at Pondok Pesantren Inklusi Nurul Maksum in Semarang, Indonesia. Results Using a qualitative descriptive-analytical approach involving interviews, participatory observation, and document analysis, the findings show that inclusive education is sustained through a layered leadership configuration encompassing transformational, charismatic, and collective leadership. Transformational leadership embeds inclusivity as an institutional vision, charismatic leadership provides moral legitimacy and social acceptance, and collective leadership operationalizes inclusive practices through collaboration and shared responsibility. Novelty The study demonstrates that sustainable inclusive Islamic education is not reliant on individual authority alone but on the institutionalization of leadership practices integrating spiritual values, symbolic authority, and participatory governance. Implications These findings contribute theoretically to Islamic educational leadership studies and offer practical insights for policymakers and practitioners seeking sustainable inclusive education models within faith-based institutions. Highlights: • Kyai leadership integrates transformational, charismatic, and collective dimensions to sustain inclusive education• Moral legitimacy and collaboration reduce resistance to inclusive practices in Islamic boarding schools• Inclusive education succeeds when leadership v Keywords: Kyai Leadership, Inclusive Education, Islamic Boarding Schools, Transformational Leadership, Collective Leadership